CRISPR/Cas12a toolbox for genome editing in Methanosarcina acetivorans - Zhu, Ping; Somvanshi, Tejas; Bao, Jichen; Scheller, Silvan (Frontiers in Microbiology, 2023)
Methanogenic archaea play an important role in the global carbon cycle and may serve as host organisms for the biotechnological production of fuels and chemicals from CO2 and other one-carbon substrates. Methanosarcina acetivorans is extensively studied as a model methanogen due to its large genome, versatile substrate range, and available genetic tools. Genome editing in M. acetivorans via CRISPR/Cas9 has also been demonstrated. Here, we describe a user-friendly CRISPR/Cas12a toolbox that recognizes T-rich (5′-TTTV) PAM sequences. The toolbox can manage deletions of 3500 bp (i.e., knocking out the entire frhADGB operon) and heterologous gene insertions with positive rates of over 80%. Cas12a-mediated multiplex genome editing was used to edit two separate sites on the chromosome in one round of editing. Double deletions of 100 bp were achieved, with 8/8 of transformants being edited correctly. Simultaneous deletion of 100 bp at one site and replacement of 100 bp with the 2400 bp uidA expression cassette at a separate site yielded 5/6 correctly edited transformants. Our CRISPR/Cas12a toolbox enables reliable genome editing, and it can be used in parallel with the previously reported Cas9-based system for the genetic engineering of the Methanosarcina species.